Mobile application development for classroom event management - Ng, Kai Yi (Nanyang Technological University, 2021)
This item explores the development of an application for Android-based devices for classroom event management. The application allows users to plan a classroom event, set up a user registration database, performing registration and attendance-taking effortlessly in real-time. The application runs in an NFC-enabled smartphone for scanning contactless smart cards for identification and registration of each participant. Alternative ways of capturing the event and participant identity, such as using a phone camera with OCR capability or scanning of QR Codes are also explored. The application is developed using the Android Studio environment and tested on an actual device.